Escherichia coli shares T- and B-lymphocyte epitopes with Schistosoma mansoni - Mahmoud Mohamed Bahgat; Hanaa Mohamed Gaber; Amany Sayed Maghraby (Journal of Infection in Developing Countries)
Background: In this study, we tested the cross-reaction between crude Escherichia coli antigen (ECA) and 3 crude Schistosoma mansoni antigens. Methodology: The schistosomal antigens used were cercarial antigen preparation (CAP), soluble worm antigen preparation (SWAP), and soluble egg antigen (SEA). Four groups each of 3 mice received 2 intraperotineal immunizations with the above-mentioned antigens at a two-week interval. The dose of the ECA was 20 μg/100 μl PBS/mouse and that of any of the used schistosomal antigens was 50 μg/100 μl PBS/mouse. IgM and IgG reactivities and cross-reactivities were tested in individual immunized mice sera (IMS) against the above-mentioned antigens by ELISA and Western blotting. The changes in the B, CD4+ and CD8+-T cells' counts post immunization were recorded. Results: Priming with ECA caused significant increases in IgM (P 0.05) against CAP and SWAP, while both priming and boosting with ECA caused a significant elevation in the IgG only against SWAP. Priming and boosting with ECA or schistosomal antigens caused significant increases in IgM against ECA. Priming with ECA or SWAP caused significant elevation in IgG against ECA. In Western blotting, ECA-IMS recognized 16, 33, 38 and 94 kDa ECA peptides that cross-reacted with CAP-IMS. ECA peptides at 30 and 38 kDa cross-reacted among ECA, SWAP and SEA-IMS. CAP peptides at 40, 71, 85 and 97 kDa cross-reacted with ECA-IMS. A 59 kDa SWAP peptide cross-reacted with ECA. SEA peptides at ~55, 96 and 101 kDa cross-reacted with ECA-IMS. Immunization with ECA, CAP, SWAP or SEA caused significant increases in mesentric lymph nodes (MLN)-CD4+, CD8+-T cells and MLN-B cells. For thymocytes, CD4+-T cells significantly increased upon immunization with ECA and SWAP while CD8+-T cells significantly increased upon immunization with SWAP. Conclusion: It is necessary to include E. coli antigens as controls while establishing schistosomal antigens-based diagnostic tests to ensure the specificity of the detected immune responses. Characterization of the cross-reactive ECA antigens with protective potential against S. mansoni infection remains a future research objective.